A meta-analysis of caspase 9 polymorphisms in promoter and exon sequence on cancer susceptibility. - Wei Xu; Shengqiang Jiang; Yuanyuan Xu; Bo Chen; Yan Li; Feng Zong; Weihong Zhao; Jianqing Wu (PLoS ONE, 2012)
BACKGROUND: Caspases are important regulators and executioners in apoptosis pathway and have been defined as either tumor suppressors or oncogenes. Polymorphisms in promoter and exon of caspase 9 were shown to confer genetic susceptibility to multiple cancers, but the results were inconsistent. To accomplish a more precise estimation of the relationship, a meta-analysis was performed. METHODOLOGY/PRINCIPAL FINDINGS: We assessed published studies of the association between caspase 9 polymorphisms and cancer risk from nine studies with 5,528 subjects for rs4645978, six studies with 2,403 subjects for rs105276 and two studies for rs4645981. Overall meta-analysis indicated that no evidence of an association between rs4645978 and cancers was found. Through the stratified analysis, statistically significant reduced cancer risks were observed among Caucasians (AG vs AA: OR = 0.81, 95% CI = 0.66-0.99, P(heterogeneity) = 0.150 and the dominant model: OR = 0.86, 95% CI = 0.75-0.99, P(heterogeneity) = 0.290) and prostate cancer. As for rs105276, Ex5+32G>A polymorphism was found with protective effect in overall meta-analysis (AA vs GG: OR = 0.75, 95% CI = 0.60-0.92, P(heterogeneity) = 0.887; A vs G: OR = 0.85, 95% CI = 0.77-0.95, P(heterogeneity) = 0.739 and the recessive model: OR = 0.68, 95% CI = 0.56-0.82, P(heterogeneity) = 0.309) and Asians group. While for rs4645981, a statistically significant increase in risk of lung cancer was shown in Asians (T vs C: OR = 1.23, 95% CI = 1.07-1.42, P(heterogeneity) = 0.399 and the dominant model: OR = 1.22, 95% CI = 1.04-1.43, P(heterogeneity) = 0.660). CONCLUSIONS/SIGNIFICANCE: Our meta-analysis suggests that the caspase 9 rs4645978 most likely contributes to decreased susceptibility to cancer in Caucasians and prostate cancer. The A allele of rs105276 might be a protective factor for cancer, especially for Asians. However, it seems that rs4645981 confers increased susceptibility to lung cancer in Asians.